A low-density weather-resistant fireproof board and preparation method thereof

Through the mixing of diatomaceous earth and quicklime and filling of alkenyl silicon aerogel, combined with kaolin and thiolated waste paper fibers, low-density weather-resistant fire-resistant plate with high strength, flexural resistance and thermal conductivity were prepared, and silicate acid was solved The problems of insufficient strength and flexural resistance of calcium fiberboard meet the requirements of fire protection acceptance of super high-rise buildings.

CN119038909BActive Publication Date: 2025-02-18INNER MONGOLIA MENGJUN CONSTRUCTION NEW MATERIALS TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411513964.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-18
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

There is still room for improvement in the strength and flexural resistance of calcium silicate fiberboard, which is difficult to meet the strict requirements for fire protection acceptance of super high-rise buildings.

Method used

Use diatomaceous earth and quicklime to obtain hollow hard silicon calcium through wet ball milling and autoclave heat treatment, and then premixed with alkenyl silicon aerogel precursor, aged and removed solvent through two-stage high-pressure solvent to form multi-stage nanopores Hard silicon calcium. Finally, it is mixed with kaolin, thiolated waste paper fiber, benzophenone and flame retardant, and a low-density weather-resistant fireproof board is obtained by press molding.

Benefits of technology

The strength, flexural performance and thermal conductivity of low-density weather-resistant fire plates are improved, and their fire resistance, weather resistance, water resistance and impact resistance are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119038909B_ABST
    Figure CN119038909B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of fireproof boards, and specifically discloses a low-density weather-resistant fireproof board and a preparation method thereof. A preparation method of a low-density weather-resistant fireproof board, using diatomaceous earth as silicon and quicklime as calcium, through wet grinding under the action of an auxiliary agent hafnium oxychloride, and heat treatment in an autoclave to obtain a hollow hard calcium silicate with a needle-like fiber surface, and then premixed with an olefinic silica aerogel precursor, aged, and then subjected to a two-stage high-pressure desolventization to obtain a multi-level nanoporous hard calcium silicate filled with olefinic silica aerogel, and finally mixed with kaolin, mercaptolated waste paper fiber, benzophenone, and flame retardant for compression molding and curing to obtain a low-density weather-resistant fireproof board. The low-density weather-resistant fireproof board prepared by the present application has the advantages of fireproof, light weight, weather resistance, water resistance, impact resistance, and strong flexural resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of fireproof boards, and more specifically, to a low-density weather-resistant fireproof board and a preparation method thereof. Background Art

[0002] At present, with the increase of super high-rise buildings in China, the requirements for fire protection acceptance of super high-rise buildings are becoming more and more stringent. For example, the reliability of smoke exhaust system and the integrity of fire partition have an important impact. Fireproof board, as a common fireproof material, is very common in construction. Fireproof board usually includes cotton board, glass wool board, cement board, perlite board, perlite board, floating bead board, vermiculite board, fireproof gypsum board, calcium silicate fiberboard and magnesium oxychloride fireproof board according to material classification. Among them, calcium silicate fiberboard is a kind of functional board with excellent performance. It is a building board mainly made of lime, silicate and inorganic fiber reinforcement materials. It has the characteristics of light weight, high strength, good thermal insulation, durability, excellent processing performance and construction performance. It is mainly used to make ceilings, partitions and as fire protection materials for steel columns and steel beams. However, the strength and flexural properties of calcium silicate fiberboard need to be improved. Summary of the invention

[0003] In order to further improve the strength and flexural resistance of calcium silicate fiberboard, the present application provides a low-density weather-resistant fireproof board and a preparation method thereof.

[0004] In the first aspect, the present application provides a method for preparing a low-density weather-resistant fireproof board, which adopts the following technical solution:

[0005] A method for preparing a low-density weather-resistant fireproof board comprises the following steps:

[0006] S1, diatomaceous earth and quicklime are mixed at a calcium-silicon ratio of (0.99-1):1, and an auxiliary agent, hafnium oxychloride, is added at a solid-liquid ratio of 1:(18-20), and wet ball milling is performed to obtain a mixed liquid;

[0007] S2, adding water to adjust the mixed liquid to a solid-liquid ratio of 1: (35-40), then placing it in an autoclave for heat treatment, cooling and filtering, and drying the obtained filter cake to obtain hollow hard calcium silicate;

[0008] S3, water, ethanol, DMF and acetic acid are uniformly mixed in proportion, and then vinyl trimethoxy silane and methyl triethoxy silane are added, hydrolyzed for 10-12 hours, and then an ammonia solution is added dropwise to obtain a vinyl silica aerogel precursor;

[0009] S4, mixing the alkenyl silica aerogel precursor and the hollow hard calcium silicate uniformly, vacuum impregnating for 5-8 hours, then placing them in ethanol, aging at 40-50°C for 5-7 days, then taking them out and placing them in a sealed autoclave for gradient heating and pressurization, and then releasing the gas to obtain multi-level nanoporous hard calcium silicate;

[0010] S5, after the waste paper fiber is ultrasonically treated with a sulfuric acid solution, it is washed to neutrality, dried, and then heated with an alkaline solution, washed again to neutrality, and dried to obtain hydroxylated waste paper fiber; 1,3-diethyltetramethyldisiloxane and γ-mercaptomethyltriethoxysilane are adjusted to pH 9-10 with acetic acid, and then the hydroxylated waste paper fiber is added, immersed for 20-24 hours, washed again to neutrality, cured and dried to obtain thiolated waste paper fiber;

[0011] S6, mix multi-level nanoporous calcium silicate, kaolin, mercaptolated waste paper fiber, benzophenone and additives, add water to adjust the liquid-solid ratio to 4-6mL / g, grind and disperse evenly, then pour into a mold, vacuum dehydrate, press-form, irradiate with ultraviolet light for 4-6h at room temperature, then steam-cure at 190-200℃ for 8-10h, and after steam-cure, dry at 100-105℃ for 20-24h to obtain a low-density weather-resistant fireproof board.

[0012] By adopting the above technical scheme, diatomaceous earth is used as silicon and quicklime is used as calcium. Under the action of auxiliary agent hafnium oxychloride, the products are wet ground and heat treated in an autoclave to obtain hollow hard calcium silicate with needle-like fibers on the surface. The products are then pre-mixed with an olefinic silica aerogel precursor, aged, and subjected to two-stage high-pressure desolventization to obtain multi-level nanoporous hard calcium silicate filled with olefinic silica aerogel. The products are finally mixed with kaolin, mercaptolated waste paper fibers, benzophenone, and flame retardants and subjected to compression molding and curing to obtain a low-density weather-resistant fireproof board.

[0013] Preferably, in S1, the addition amount of hafnium oxychloride is 1-2%, the ball milling speed is 280-320 r / min, and the ball milling time is 15-30 min.

[0014] Preferably, in S2, the heat treatment temperature is 200-230°C, the stirring speed in the autoclave is 300-500r / min, the heat treatment time is 6-8h, the filter cake drying temperature is 100-110°C, and the drying time is 12-18h.

[0015] By adopting the above technical solution, under this condition, the surface of the prepared hollow hard calcium silicate is needle-like fiber with high strength and light weight.

[0016] Preferably, in S3, the molar ratio of water, ethanol, DMF, acetic acid, vinyltrimethoxysilane and methyltriethoxysilane is (8-10):(7-9):(0.75-0.80):(0.6-0.65):(0.06-0.08):1, the ratio of ammonia solution to methyltriethoxysilane is (3.5-4.8) mL:(1-1.2) mg, and the concentration of ammonia solution is 8-10 mol / L.

[0017] By adopting the above technical solution, the obtained alkenyl silica aerogel precursor has a better flow state, which is beneficial to the subsequent impregnation operation.

[0018] Preferably, in S4, the usage ratio of alkenyl silica aerogel precursor and hollow hard calcium silicate is (40-60) mL: (8-12) g.

[0019] By adopting the above technical solution, at this ratio, the vinyl silica aerogel precursor can meet the filling requirements of hollow hard calcium silicate.

[0020] Preferably, in S4, the procedure of gradient heating and pressurization is: first, keep warm at 5-6 MPa, 180-200°C for 4-6 hours, and then keep warm at 12-20 MPa, 250-300°C for 2-3 hours.

[0021] By adopting the above technical solution, under this condition, multi-level nanoporous hard calcium silicate can be obtained.

[0022] Preferably, in S5, the concentration of the sulfuric acid solution is 4-6 g / L; the alkaline solution is a sodium hydroxide solution with a concentration of 10-12 g / L; the mass volume ratio of waste paper fiber, sulfuric acid solution, and alkaline solution is (18-25) mL: (4-6) g: (18-25) mL; the mass ratio of 1,3-diethyltetramethyldisiloxane to γ-mercaptopropyltrimethoxysilane and hydroxylated waste paper fiber is (10-12): (11-14): (15-18).

[0023] By adopting the above technical solution, after the waste paper fibers are hydroxylated, it is beneficial to achieve the thiolization of the waste paper fibers.

[0024] Preferably, in S6, the mass ratio of multi-level nanoporous calcium silicate, kaolin, mercaptolated waste paper fiber, benzophenone and additive is (45-65):(13-18):(16-20):(3-5):(1-3).

[0025] By adopting the above technical solution and using benzophenone as an initiator, it is beneficial for the mercapto group to react with the alkenyl group on the surface of the multi-level nanoporous hard calcium silicate to form a chemical bond under ultraviolet light.

[0026] Preferably, the additive is a flame retardant, and the flame retardant is an inorganic flame retardant.

[0027] By adopting the above technical solution, the fireproof performance of the low-density weather-resistant fireproof board can be further enhanced.

[0028] In a second aspect, the present application provides a low-density weather-resistant fireproof board, which is obtained by the above-mentioned preparation method.

[0029] In summary, this application has the following beneficial effects:

[0030] 1. The present application adopts diatomaceous earth as silicon and quicklime as calcium, which are wet-ground under the action of auxiliary agent hafnium oxychloride, and heat-treated in an autoclave to obtain a hollow hard calcium silicate with a needle-like fiber surface. The hollow calcium silicate is then pre-mixed with an olefinic silica aerogel precursor, aged, and then subjected to a two-stage high-pressure desolventization to obtain a multi-level nanoporous hard calcium silicate filled with olefinic silica aerogel. Finally, the hollow calcium silicate is mixed with kaolin, thiolated waste paper fiber, benzophenone, and a flame retardant, and subjected to compression molding and curing to obtain a low-density weather-resistant fireproof board.

[0031] 2. In the present application, diatomaceous earth is used as silicon and hafnium oxychloride is used as an auxiliary agent to prepare hard calcium silicate with a high-strength hollow structure to improve the strength of low-density weather-resistant fireproof boards. The elasticity is increased by filling alkenyl silica aerogel to improve the folding strength of low-density weather-resistant fireproof boards. Multi-level nanoporous hard calcium silicate is prepared by two-stage thermal insulation to improve the thermal conductivity of low-density weather-resistant fireproof boards. By thiolation of waste paper fibers, on the one hand, the thiol groups react with the alkenyl groups on the surface of the multi-level nanoporous hard calcium silicate under ultraviolet light to form chemical bonds, and on the other hand, the waste paper fibers are hydrated and wrapped with the multi-level nanoporous hard calcium silicate to achieve dual physical and chemical fixation, thereby further improving the impact strength and folding resistance of the low-density weather-resistant fireproof boards.

[0032] 3. The low-density weather-resistant fireproof board prepared by the preparation method of the present application has good fire resistance, light weight, weather resistance, water resistance, impact resistance and strong flexural resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 : SEM images of the hollow hard calcium silicate prepared by Example 2, Comparative Example 1 and Comparative Example 2 of the present application, wherein the left (enlarged size 10 μm) is Example 2, the middle (enlarged size 10 μm) is Comparative Example 1, and the right (enlarged size 10 μm) is Comparative Example 2.

[0034] Figure 2 : SEM images of the multi-level nanoporous hard calcium silicate prepared in Example 2 of the present application, including the left (magnified size 10μm), the middle (magnified size 100nm), and the right (magnified size 200nm).

[0035] Figure 3: SEM images of the cross-sectional morphology of the low-density weather-resistant fireproof board prepared in Example 2 of the present application, wherein the left (enlarged size 50 μm), the right (enlarged size 500 nm). DETAILED DESCRIPTION

[0036] The present application is further described in detail below with reference to the embodiments.

[0037] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0038] Hafnium oxychloride was purchased from Exploration Platform (Shanghai Titan Technology Co., Ltd.), product number: 013668019, CAS14456-34-9.

[0039] Example 1: The low-density weather-resistant fireproof board of this example is prepared by the following method:

[0040] S1, diatomite and quicklime are mixed at a calcium-silicon ratio of 0.99:1, and an auxiliary agent, hafnium oxychloride, is added at a solid-liquid ratio of 1:18, and the amount of hafnium oxychloride added is 1% of the solid mass, and wet-milled in a ball mill at a ball milling speed of 280 r / min and a ball milling time of 15 min to obtain a mixed liquid;

[0041] S2, adding water to adjust the mixed liquid to a solid-liquid ratio of 1:35, then placing it in an autoclave for heat treatment, cooling and filtering, and drying the obtained filter cake to obtain hollow hard calcium silicate; the heat treatment temperature is: 200°C, the stirring speed in the autoclave is 300r / min, the heat treatment time is 6h, the filter cake drying temperature is 100°C, and the drying time is 12h;

[0042] S3, water, ethanol, DMF and acetic acid are uniformly mixed in proportion, then vinyl trimethoxy silane and methyl triethoxy silane are added, hydrolyzed for 10 hours, and then an ammonia solution is added dropwise to obtain an vinyl silicon aerogel precursor; the molar ratio of water, ethanol, DMF, acetic acid, vinyl trimethoxy silane and methyl triethoxy silane is 8:7:0.75:0.6:0.06:1, the ratio of ammonia solution to methyl triethoxy silane is 3.5 mL:1 mg, and the concentration of ammonia solution is 8 mol / L;

[0043] S4, the alkenyl silica aerogel precursor and the hollow hard calcium silicate are mixed evenly, vacuum impregnated for 5 hours, and then placed in ethanol 50 times the mass of the alkenyl silica aerogel precursor, aged at 40°C for 7 days, and then taken out and placed in a sealed autoclave, first at 5MPa, 200°C for 4 hours, and then at 12Mpa, 300°C for 2 hours, and then the gas is released to obtain multi-level nanoporous hard calcium silicate; the usage ratio of alkenyl silica aerogel precursor and hollow hard calcium silicate is 40mL:8g;

[0044] S5, after the waste paper fiber is ultrasonically treated with sulfuric acid solution, it is washed with water until neutral, dried, and then added with alkaline solution and kept at 100°C for 40 minutes, washed with water again to neutralize, and dried at 55°C for 8 hours to obtain hydroxylated waste paper fiber; 1,3-diethyltetramethyldisiloxane and γ-mercaptomethyltriethoxysilane are adjusted to pH 9 with acetic acid, and then added to the hydroxylated waste paper fiber, immersed for 20 hours, washed with water again to neutralize, cured and dried to obtain mercaptolated waste paper fiber; the concentration of sulfuric acid solution is 4g / L; the alkaline solution is sodium hydroxide solution, and the concentration is 10g / L; the mass volume ratio of waste paper fiber, sulfuric acid solution, and alkaline solution is 18mL:4g:18mL; the mass ratio of 1,3-diethyltetramethyldisiloxane to γ-mercaptopropyltrimethoxysilane and hydroxylated waste paper fiber is 10:11:15;

[0045] S6, mix multi-level nanoporous hard calcium silicate, kaolin, thiolated waste paper fiber, benzophenone, and flame retardant, add water to adjust the liquid-to-solid ratio to 4 mL / g, grind and disperse evenly, then pour into a mold, vacuum dehydrate, press-form, irradiate with ultraviolet light for 4 hours at room temperature, then steam-cure at 190°C for 10 hours, and after steaming, dry at 100°C for 24 hours to obtain a low-density weather-resistant fireproof board; the mass ratio of multi-level nanoporous hard calcium silicate, kaolin, thiolated waste paper fiber, benzophenone, and flame retardant is 45:13:16:3:1.

[0046] Example 2: The low-density weather-resistant fireproof board of this example is prepared by the following method:

[0047] S1, diatomite and quicklime are mixed at a calcium-silicon ratio of 1:1, and an auxiliary agent, hafnium oxychloride, is added at a solid-liquid ratio of 1:19, and the amount of hafnium oxychloride added is 1.5% of the solid mass, and wet-milled in a ball mill at a ball milling speed of 300 r / min for 20 min to obtain a mixed liquid;

[0048] S2, adding water to adjust the mixed liquid to a solid-liquid ratio of 1:38, then placing it in an autoclave for heat treatment, cooling and filtering, and drying the obtained filter cake to obtain hollow hard calcium silicate; the heat treatment temperature is: 220°C, the stirring speed in the autoclave is 400r / min, the heat treatment time is 7h, the filter cake drying temperature is 105°C, and the drying time is 15h;

[0049] S3, water, ethanol, DMF and acetic acid are uniformly mixed in proportion, then vinyl trimethoxy silane and methyl triethoxy silane are added, hydrolyzed for 11 hours, and then an ammonia solution is added dropwise to obtain an vinyl silicon aerogel precursor; the molar ratio of water, ethanol, DMF, acetic acid, vinyl trimethoxy silane and methyl triethoxy silane is 9:8:0.78:0.63:0.07:1, the ratio of ammonia solution to methyl triethoxy silane is 4.2 mL:1.1 mg, and the concentration of ammonia solution is 9 mol / L;

[0050] S4, the alkenyl silica aerogel precursor and the hollow hard calcium silicate are mixed evenly, vacuum impregnated for 6 hours, and then placed in ethanol 50 times the mass of the alkenyl silica aerogel precursor, aged at 45°C for 6 days, and then taken out and placed in a sealed autoclave, first kept at 5.5MPa, 190°C for 5 hours, and then kept at 18Mpa, 280°C for 3 hours, and then released the gas to obtain hierarchical nanoporous hard calcium silicate; the dosage ratio of alkenyl silica aerogel precursor and hollow hard calcium silicate is 50mL:10g; the pore size of the hierarchical nanoporous hard calcium silicate measured by nitrogen adsorption method is 78% concentrated in the range of 10-40nm, and 15% concentrated in the range of 60-80nm;

[0051] S5, after the waste paper fiber is ultrasonically treated with sulfuric acid solution, it is washed with water until neutral, dried, and then added with alkaline solution and kept at 100°C for 40 minutes, washed with water again to neutralize, and dried at 55°C for 8 hours to obtain hydroxylated waste paper fiber; 1,3-diethyltetramethyldisiloxane and γ-mercaptomethyltriethoxysilane are adjusted to pH 9 with acetic acid, and then added to the hydroxylated waste paper fiber, immersed for 22 hours, washed with water again to neutralize, cured and dried to obtain mercaptolated waste paper fiber; the concentration of sulfuric acid solution is 5g / L; the alkaline solution is sodium hydroxide solution, and the concentration is 11g / L; the mass volume ratio of waste paper fiber, sulfuric acid solution, and alkaline solution is 20mL:5g:20mL; the mass ratio of 1,3-diethyltetramethyldisiloxane to γ-mercaptopropyltrimethoxysilane and hydroxylated waste paper fiber is 11:13:17;

[0052] S6, mix multi-level nanoporous calcium silicate, kaolin, thiolated waste paper fiber, benzophenone, and flame retardant, add water to adjust the liquid-solid ratio to 5 mL / g, grind and disperse evenly, then pour into a mold, vacuum dehydrate, press-form, irradiate with ultraviolet light for 5 hours at room temperature, then steam-cure at 195°C for 9 hours, and after steaming, dry at 105°C for 22 hours to obtain a low-density weather-resistant fireproof board; the mass ratio of multi-level nanoporous calcium silicate, kaolin, thiolated waste paper fiber, benzophenone, and additives is 55:15:18:4:2.

[0053] Example 3: The low-density weather-resistant fireproof board of this example is prepared by the following method:

[0054] S1, diatomite and quicklime are mixed at a calcium-silicon ratio of 1:1, and an auxiliary agent, hafnium oxychloride, is added at a solid-liquid ratio of 1:20, and the amount of hafnium oxychloride added is 2% of the solid mass, and wet-milled in a ball mill at a ball milling speed of 320 r / min for 30 min to obtain a mixed liquid;

[0055] S2, adding water to adjust the mixed liquid to a solid-liquid ratio of 1:40, then placing it in an autoclave for heat treatment, cooling and filtering, and drying the obtained filter cake to obtain hollow hard calcium silicate; the heat treatment temperature is: 230°C, the stirring speed in the autoclave is 500r / min, the heat treatment time is 8h, the filter cake drying temperature is 110°C, and the drying time is 18h;

[0056] S3, water, ethanol, DMF and acetic acid are uniformly mixed in proportion, then vinyl trimethoxy silane and methyl triethoxy silane are added, hydrolyzed for 12 hours, and then an ammonia solution is added dropwise to obtain an vinyl silicon aerogel precursor; the molar ratio of water, ethanol, DMF, acetic acid, vinyl trimethoxy silane and methyl triethoxy silane is 10:9:0.80:0.65:0.08:1, the ratio of ammonia solution to methyl triethoxy silane is 4.8 mL:1.2 mg, and the concentration of ammonia solution is 10 mol / L;

[0057] S4, the alkenyl silica aerogel precursor and the hollow hard calcium silicate are mixed evenly, vacuum impregnated for 8 hours, and then placed in ethanol 50 times the mass of the alkenyl silica aerogel precursor, aged at 50°C for 5 days, and then taken out and placed in a sealed autoclave, first at 6MPa, 180°C for 6 hours, and then at 20Mpa, 250°C for 3 hours, and then the gas is released to obtain multi-level nanoporous hard calcium silicate; the usage ratio of alkenyl silica aerogel precursor and hollow hard calcium silicate is 60mL:12g;

[0058] S5, after the waste paper fiber is ultrasonically treated with sulfuric acid solution, it is washed with water until neutral, dried, and then added with alkaline solution and kept at 100°C for 40 minutes, washed with water again to neutralize, and dried at 55°C for 8 hours to obtain hydroxylated waste paper fiber; 1,3-diethyltetramethyldisiloxane and γ-mercaptomethyltriethoxysilane are adjusted to pH 10 with acetic acid, and then added to the hydroxylated waste paper fiber, immersed for 24 hours, washed with water to neutralize, cured and dried to obtain mercaptolated waste paper fiber; the concentration of sulfuric acid solution is 6g / L; the alkaline solution is sodium hydroxide solution, and the concentration is 12g / L; the mass volume ratio of waste paper fiber, sulfuric acid solution, and alkaline solution is 25mL:6g:25mL; the mass ratio of 1,3-diethyltetramethyldisiloxane to γ-mercaptopropyltrimethoxysilane and hydroxylated waste paper fiber is 12:14:18;

[0059] S6, mix multi-level nanoporous hard calcium silicate, kaolin, thiolated waste paper fiber, benzophenone, and flame retardant, add water to adjust the liquid-solid ratio to 6 mL / g, grind and disperse evenly, then pour into a mold, vacuum dehydrate, press-form, irradiate with ultraviolet light for 6 hours at room temperature, then steam-cure at 200°C for 8 hours, and after steaming, dry at 105°C for 20 hours to obtain a low-density weather-resistant fireproof board; the mass ratio of multi-level nanoporous hard calcium silicate, kaolin, thiolated waste paper fiber, benzophenone, and additives is 65:18:20:5:3.

[0060] Comparative Example 1: The method for preparing the low-density weather-resistant fireproof board in this comparative example is different from that in Example 2 in that hafnium oxychloride is not added.

[0061] Comparative Example 2: The method for preparing the low-density weather-resistant fireproof board in this comparative example is different from that in Example 2 in that silica fume is used instead of diatomaceous earth.

[0062] Comparative Example 3: The preparation method of the low-density weather-resistant fireproof board of this comparative example is different from that of Example 2 in that, in S4, the autoclave adopts a one-stage hot pressing treatment, and the specific operation is as follows: the alkenyl silica aerogel precursor and the hollow hard calcium silicate are mixed evenly, vacuum impregnated for 6 hours, and then placed in ethanol 50 times the mass of the alkenyl silica aerogel precursor, aged at 45°C for 6 days, and then taken out and placed in an autoclave seal, first at 5.5MPa, 190°C for 5 hours, and then at 18Mpa, 280°C for 3 hours, and then release the gas to obtain nanoporous hard calcium silicate; the ratio of alkenyl silica aerogel precursor to hollow hard calcium silicate is 50mL:10g. The pore size of the nanoporous hard calcium silicate measured by nitrogen adsorption method is 85% concentrated in the range of 55-100nm.

[0063] In the subsequent preparation of low-density weather-resistant and fire-proof boards, nanoporous hard calcium silicate is used instead of multi-level nanoporous hard calcium silicate.

[0064] Comparative Example 4: The method for preparing the low-density weather-resistant fireproof board in this comparative example is different from that in Example 2 in that the alkenyl silica aerogel and the hollow hard calcium silicate are directly added together with other raw materials to prepare the low-density weather-resistant fireproof board. The specific operation is as follows:

[0065] S4, placing the alkenyl silica aerogel precursor in ethanol with a mass 50 times that of the alkenyl silica aerogel precursor, aging at 45°C for 6 days, then taking it out and placing it in a sealed autoclave, first keeping it at 5.5MPa, 190°C for 5h, then keeping it at 18Mpa, 280°C for 3h, and then releasing the gas to obtain alkenyl silica aerogel;

[0066] S6, mix alkenyl silica aerogel, hollow hard calcium silicate, kaolin, thiolated waste paper fiber, benzophenone and flame retardant, add water to adjust the liquid-to-solid ratio to 5 mL / g, grind and disperse evenly, then pour into a mold, vacuum dehydrate, press-form, irradiate with ultraviolet light for 5 hours at room temperature, then steam-cure at 195°C for 9 hours, and after steaming, dry at 105°C for 22 hours to obtain a low-density weather-resistant fireproof board; the mass ratio of alkenyl silica aerogel, hollow hard calcium silicate, kaolin, thiolated waste paper fiber, benzophenone and additives is 10:45:15:18:4:2.

[0067] 1. Microscopic morphology:

[0068] a. Using an electron scanning electron microscope, the microscopic morphology of the hollow hard calcium silicate prepared in Example 2, Comparative Example 1 and Comparative Example 2 was observed. The results are as follows Figure 1 (The left is Example 2, the middle is Comparative Example 1, and the right is Comparative Example 2). Figure 1 As can be seen from the left, the hollow hard calcium silicate prepared by using diatomite and auxiliary agent hafnium oxychloride is spherical as a whole, with a needle-like fiber aggregate on the surface and an obvious hollow structure; Figure 1 It can be seen that adding the auxiliary agent hafnium oxychloride is the key to obtaining hollow hard calcium silicate; Figure 1 As can be seen on the right, although a hollow structure can be obtained by using silica fume as the silica, the needle-like fibrous crystals on its surface are poorly developed.

[0069] b. Using an electron scanning electron microscope, the microscopic morphology of the multi-level nanoporous hard calcium silicate prepared in Example 2 was observed. Figure 2 As shown. Figure 2 It can be seen from Figure 2 As can be seen from the left, the hollow part of the hollow calcium silicate of the needle-like fiber is filled with vinyl silica aerogel; Figure 2 It can be seen that the filled alkenyl silica aerogel has a nanoporous structure; Figure 2 As can be seen from the right, the hard calcium silicate fiber and the nanoporous vinyl silica aerogel are well combined together at the bonding interface between the two, forming a nanoporous structure with multi-level pore sizes.

[0070] c. Using an electron scanning electron microscope, the cross-sectional morphology of the low-density weather-resistant fireproof board prepared in Example 2 was observed, and the results were as follows Figure 3 As shown. Figure 3 From the middle left, it can be seen that the thiolated waste paper fibers are evenly distributed in the low-density weather-resistant fireproof board; Figure 3 As can be seen in the middle right, the thiolated waste paper fibers and the multi-level nanoporous hard calcium silicate are combined with each other to form a network pore structure.

[0071] 2. Performance testing:

[0072] d. Performance test: The low-density weather-resistant fireproof boards prepared in Examples 1 to 3 and Examples 1 to 4 were subjected to performance tests according to the test standards and test methods in JC-T564.1-2018. The results are shown in Table 1:

[0073] Table 1. Performance test

[0074] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 <![CDATA[Apparent density (g / cm 3 )]]> 0.66 0.63 0.69 1.03 0.94 0.71 0.68 Thermal conductivity (W / m / K) 0.052 0.048 0.055 0.143 0.098 0.071 0.062 Wet expansion rate (%) 0.12 0.11 0.14 0.15 0.14 0.12 0.15 Non-flammable Level A1 Level A1 Level A1 Level A1 Level A1 Level A1 Level A1 Waterproof No water drops No water drops No water drops No water drops No water drops No water drops No water drops Frost resistance-flexural strength ratio (%) 89.1 93.2 88.9 82.6 84.5 83.4 80.9 Thermal rain-flexural strength ratio (%) No cracking, no delamination No cracking, no delamination No cracking, no delamination There are cracks, no delamination No cracking, no delamination No cracking, no delamination No cracking, no delamination Hot water-flexural strength ratio (%) 83.2 85.3 84.6 73.7 78.4 79.5 70.2 Dry-flexural strength (MPa) 18.5 17.8 18.3 10.3 12.3 14.6 9.3 Saturated-flexural strength (MPa) 23.6 22.5 23.1 12.7 14.5 16.3 11.8 <![CDATA[Impact strength (kJ / m 2 )]]> 6.8 7.1 7.3 3.5 4.6 6.1 5.5

[0075] It can be seen from Table 1 that the low-density weather-resistant fireproof boards prepared in Examples 1 to 3 of the present application have good fireproofing properties, as well as light weight, weather resistance, water resistance, impact resistance and strong flexural resistance, indicating that the low-density weather-resistant fireproof boards prepared in Examples 1 to 3 of the present application have good fireproofing properties. Combining Comparative Examples 1 and 2, it can be seen that the preparation quality of hollow hard calcium silicate has a great influence on the comprehensive performance of low-density weather-resistant fireproof boards. Combining Comparative Examples 3 and 4, it can be seen that the multi-stage nanoporous hard calcium silicate prepared by two-stage heating has a smaller thermal coefficient and lower density. The fireproof board prepared by pre-filling hollow hard calcium silicate with alkenyl silica aerogel precursor has higher flexural resistance than the method of adding alkenyl silica aerogel, hollow hard calcium silicate and other raw materials at the same time.

[0076] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, a person skilled in the art may make non-creative modifications to the present embodiment as needed, and such modifications shall be protected by the patent law as long as they are within the scope of protection claimed in the present application.

Claims

1. A method for preparing a low-density weather-resistant fireproof board, characterized in that: The following steps are involved: S1, diatomaceous earth and quicklime are mixed at a calcium-silicon ratio of (0.99-1):1, and an auxiliary agent, hafnium oxychloride, is added at a solid-liquid ratio of 1:(18-20), and wet ball milling is performed to obtain a mixed liquid; S2, adding water to adjust the mixed liquid to a solid-liquid ratio of 1: (35-40), then placing it in an autoclave for heat treatment, cooling and filtering, and drying the obtained filter cake to obtain hollow hard calcium silicate; S3, water, ethanol, DMF and acetic acid are uniformly mixed in proportion, and then vinyl trimethoxy silane and methyl triethoxy silane are added, hydrolyzed for 10-12 hours, and then an ammonia solution is added dropwise to obtain an vinyl silica aerogel precursor; S4, mixing the alkenyl silica aerogel precursor and the hollow hard calcium silicate uniformly, vacuum impregnating for 5-8 hours, then placing them in ethanol, aging at 40-50°C for 5-7 days, then taking them out and placing them in a sealed autoclave for gradient heating and pressurization, and then releasing the gas to obtain multi-level nanoporous hard calcium silicate; S5, after the waste paper fiber is ultrasonically treated with a sulfuric acid solution, it is washed to neutrality, dried, and then heated with an alkaline solution, washed again to neutrality, and dried to obtain hydroxylated waste paper fiber; 1,3-diethyltetramethyldisiloxane and γ-mercaptomethyltriethoxysilane are adjusted to pH 9-10 with acetic acid, and then the hydroxylated waste paper fiber is added, immersed for 20-24 hours, washed again to neutrality, cured and dried to obtain thiolated waste paper fiber; S6, mixing multi-level nanoporous calcium silicate, kaolin, mercaptolated waste paper fiber, benzophenone and additives, adding water to adjust the liquid-solid ratio to 4-6 mL / g, grinding and dispersing evenly, then pouring into a mold, vacuum dehydrating, press-molding, irradiating with ultraviolet light for 4-6 hours at room temperature, and then steaming at 190-200° C. for 8-10 hours, and drying at 100-105° C. for 20-24 hours after the steaming, to obtain a low-density weather-resistant fireproof board; In S1, the added mass of hafnium oxychloride is 1-2% of the solid mass; In S3, the molar ratio of water, ethanol, DMF, acetic acid, vinyltrimethoxysilane and methyltriethoxysilane is (8-10):(7-9):(0.75-0.80):(0.6-0.65):(0.06-0.08):1, the ratio of ammonia solution to methyltriethoxysilane is (3.5-4.8) mL:(1-1.2) mg, and the concentration of ammonia solution is 8-10 mol / L; In the S4, the amount ratio of the alkenyl silica aerogel precursor and the hollow hard calcium silicate is (40-60) mL: (8-12) g; In S5, the concentration of the sulfuric acid solution is 4-6 g / L; the alkaline solution is a sodium hydroxide solution with a concentration of 10-12 g / L; the mass volume ratio of the waste paper fiber, the sulfuric acid solution, and the alkaline solution is (18-25) mL: (4-6) g: (18-25) mL; the mass ratio of 1,3-diethyltetramethyldisiloxane to γ-mercaptopropyltrimethoxysilane and hydroxylated waste paper fiber is (10-12): (11-14): (15-18); In the S6, the mass ratio of multi-level nanoporous calcium silicate, kaolin, mercaptolated waste paper fiber, benzophenone, and additives is (45-65): (13-18): (16-20): (3-5): (1-3).

2. The method for preparing a low-density weather-resistant fireproof board according to claim 1, characterized in that: In S1, the ball milling speed is 280-320 r / min, and the ball milling time is 15-30 min.

3. The method for preparing a low-density weather-resistant fireproof board according to claim 2, characterized in that: In S2, the heat treatment temperature is 200-230°C, the stirring speed in the autoclave is 300-500r / min, the heat treatment time is 6-8h, the filter cake drying temperature is 100-110°C, and the drying time is 12-18h.

4. The method for preparing a low-density weather-resistant fireproof board according to claim 3, characterized in that: In S4, the procedure of gradient heating and pressurization is: first, keep warm at 5-6 MPa, 180-200°C for 4-6 hours, and then keep warm at 12-20 MPa, 250-300°C for 2-3 hours.

5. The method for preparing a low-density weather-resistant fireproof board according to claim 4, characterized in that: The additive is a flame retardant.

6. A low-density weather-resistant fireproof board, characterized in that: The method is prepared according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Preparation method of porous xonotlite

    CN115259170A

  • Prepn process of super heat insulating material of composite nanometer pore calcium silicate

    CN1636917A